Radial basis function network for speech pattern classification - Renals, Steve (IEE, 1989)
A neural network model incorporating radial basis functions is used in a speech-pattern classification problem. The method is compared with a back-propagation neural network model and with a vector-quantised hidden Markov model of the same problem. Training times are over an order of magnitude faster, with similar classification results